2001
DOI: 10.4049/jimmunol.166.5.3143
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Function of T1/ST2 Expression on CD4+ T Cells: Induction of Type 2 Cytokine Production by T1/ST2 Cross-Linking

Abstract: The orphan receptor T1/ST2, a member of the IL-1R family, is preferentially expressed on the surface of murine Th2 cells. In this study, we analyzed the kinetics and function of T1/ST2 expression on Th2 cells in vitro. Whereas naive CD4+ cells did not express T1/ST2, most CD4+ cells became T1/ST2+ upon repeated antigenic stimulation under Th2-polarizing conditions. Flow cytometric analyses revealed that the kinetics of T1/ST2 expression on Th2 cells was delayed compared with the kinetics of type 2 cytokine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 31 publications
8
88
0
3
Order By: Relevance
“…T1/ST2 is the ligand-binding portion of the IL-33 receptor and is reported to promote Th2 responses and inhibit inflammatory responses [6,[9][10][11][12]. In this study we demonstrate that BALB/c mice infected with T. gondii have increased T1/ST2 mRNA transcripts in the brain suggestive of a role for this molecule during infection.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…T1/ST2 is the ligand-binding portion of the IL-33 receptor and is reported to promote Th2 responses and inhibit inflammatory responses [6,[9][10][11][12]. In this study we demonstrate that BALB/c mice infected with T. gondii have increased T1/ST2 mRNA transcripts in the brain suggestive of a role for this molecule during infection.…”
Section: Discussionsupporting
confidence: 50%
“…T1/ST2 is expressed by a number of haematopoetic cells such as T cells, mast cells, macrophages, NK cells and invariant NKT cells [3][4][5][6][7]. ST2L has previously been used as a marker for Th2 cells although T1/ST2-negative Th2 cells exist with reports that ST2L may be better described as a marker of effector Th2 cells enhancing the Th2 response rather than aiding its development [3,[8][9][10]. As well as promoting a Th2 response ST2L has been shown to sequester the signalling molecules MyD88 and Mal to inhibit subsequent cytokine production following TLR ligation [10].…”
Section: Introductionmentioning
confidence: 99%
“…17 Following IL-33 treatment the total peritoneal T-cell numbers were not different compared to control treated animals (Figure 3a). However, in the IL-33 treated mice, CD4 T-cells were overrepresented as the animals exhibited a significant decrease of CD8 T-cells locally (Figure 3b &c ).…”
Section: Resultsmentioning
confidence: 88%
“…2 ST2 (also known as IL-1RL1, DER4, T1 and FIT-1) belongs to the Toll-like/IL-1 receptor superfamily. [3][4][5] It has been well documented to be the cellular marker for differentiated T helper 2 (Th2) cells 6,7 and to be expressed on mast cells. 8,9 As a nuclear factor, the intracellular functions of IL-33 remain to be further clarified, although overexpression studies suggested a role as a transcriptional repressor.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 As a nuclear factor, the intracellular functions of IL-33 remain to be further clarified, although overexpression studies suggested a role as a transcriptional repressor. 10 As an extracellular cytokine, binding of IL-33 to the ST2 receptor activates nuclear factor-kB and mitogen-activated protein kinases, [3][4][5]11 and is involved in the polarization of T cells towards the Th2 cell phenotype 2,6,7,[11][12][13][14] and in activation of mast cells, [15][16][17][18][19][20] bosophils, 14,[20][21][22][23][24] eosinophils, [24][25][26] and natural killer cells. 14,27 IL-33 must be present extracellularly in order to play the crucial role in inflammatory, infectious and autoimmune diseases including anaphylactic shock, asthma, rheumatoid arthritis, atherosclerosis, systemic sclerosis and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%